BERAT BADAN AKHIR, KONVERSI RANSUM DAN INCOME OVER FEED AND CHICK COST AYAM BROILER DENGAN PEMBERIAN RANSUM KOMERSIAL - Kiramang, Khaerani (Teknosains, 2011)
The aim of this study to determine the effect of feeding commercial rations on the final live weight, feed conversion and "income over feed and chick cost".This study uses 90 mixed sex chicken experiment with strain "Arbor acres" 707 SR. It produced of PT. Satwa Utama Raya (SUR), Maros and maintained for 6 weeks. They treatmented with 3 (three) rations : 1) Rx = feeding Â rations manufactured by PT. X, 2) Ry = feeding rations manufactured by Â PT. Y and 3) Rz = feeding rations manufactured by PT. Z. There are 5 (five) repetition for each treatment. The parameters are the final live weight, feed conversion and "income over feed and chick cost". The data are processed with a range of RAL and continued analysis of LSD when the results are significant.The result showed that the use of commercial rations are not significant to the final live weight, feed conversion and âincome over feed and chick cost.